Atuação docente de professores de educação física de escolas públicas de ensino médio de Santa Maria/RS - Neu, Adriana Flávia (2018)
The research reported in this text was developed within the scope of the Study Group, Research and Interventions “Inovação Educacional, Práticas Educativas e Formação de Professores”, hosted at the Center for Studies in Education, Science and Culture of the UFSM Education Center, and had as objective the establishment of a characterization of the teaching performance of teachers of Physical Education of Public Schools of High School. For the development, we elaborated the following research problem: What are the main aspects of the teaching practices of Physical Education developed in Public High Schools situated in Santa Maria/RS? In order to try to answer the elaborated research problem and, consequently, to reach the proposed objective, we elaborated five research questions, namely: (1) What assumptions usually support the teaching practices of Physical Education teachers developed in Public Schools of High School? (2) How do Physical Education teachers usually select contents and organize curricular programs for Physical Education in High School Public Schools? (3) How are the educational activities in the scope of Physical Education in High School Public Schools organized and developed? (4) How are assessments in Physical Education classes usually held in public high schools?, and (5) What actions are usually carried out in Public High Schools in the scope of the teaching work of Physical Education teachers? This research is of a qualitative nature, and the treatment of the information collected was done based on the assumptions and the orientations present in the Grounded Theory. For the process of information collection/construction, we use as sources: (1) in the subject kind, Physical Education teachers; and (2) in the space kind, classes taught by these Physical Education teachers. The instruments used to collect/construct information were: interview, for teachers, and observation for the classes taught by them. For the development of the empirical part of this research, we chose the context of Public High Schools located in the city of Santa Maria, belonging to State Public School Network of Rio Grande do Sul. In the total, we were able to carry out 06 interviews with these teachers and also observed a set of 30 classes taught by 04 of these interviewed teachers. From the analysis of the collected/constructed information, we came to the realization that the teachers: (1) seek to meet their training needs to overcome gaps left by their Bachelor's Degree; (2) usually incorporate elements of the School's Political Pedagogical Project (PPP) to teach the school subject; (3) they usually use some elements of the didactic approaches presented in the specialized literature for the teaching of Physical Education in the school; (4) they usually take the Referencial Curricular system of Rio Grande do Sul as the main guiding document for the selection of contents and organization of curricular programs, followed by indications from their own experiences, as well as the results of dialogues with their professional colleagues; (5) they usually consider the weekly workload usually allocated to Physical Education as adequate and sufficient to develop the programmed content; (6) consider the devaluation of the education professional as a complicating factor for the quality of the discipline's development; (7) consider the joint work among teachers as practically nonexistent in the schools in which they work; (8) they usually plan, for the development of the school physical Education, education contents that revolve around the traditional collective sports (soccer, volleyball, basketball and handball) and that deal with transversal themes suggested by the PPP of their schools and/or by the the Referencial Curricular system of RS; (9) usually use forms of evaluation that contemplate three types of content (conceptual, procedural and attitudinal); (10) are able to verbalize indicators of expected learning to evaluate their students, as even as in the succinct form; (11) usually participate in pedagogical meetings offered by schools; and (12) usually develop and develop extracurricular activities in the schools where they work. To the end, it is possible to affirm that Physical Education teachers mobilize varied teaching knowledge during their teaching performance, as well as the results of this research can contribute to the professionalization of Physical Education teaching.